PENDAMPINGAN PEMBUATAN DAN PERHITUNGAN SEDERHANA NILAI PRODUK PAKAN WAFER PADA KELOMPOK TERNAK SAPI TRADISIONAL DI KEPULAUAN MERANTI - Azlina, Nur; Noviasari, Henni; Hellyward, James; Erwan, Edi; Desmiyawati, Desmiyawati; Iznillah, Muhammad Luthfi; Amri, Taqiyuddin; Yananta Sari, Debyta; Azahra, Mutiara (Jurnal Abdi Insani, 2025)
Gogok Darussalam Village, located in Tebing Tinggi Barat District, Kepulauan Meranti Regency, possesses significant potential in sago crop production. The high volume of production results in an abundance of sago pulp waste, which can be utilized as raw material for the production of wafer-based cattle feed. This community service activity aimed to evaluate the formulation of wafer feed and assess the product's value in improving cattle weight gain. The program employed a Community-Based Research (CBR) approach, which actively involves the local community in every stage of the activity, thereby contributing to positive social change. The results of the activity indicated that this research-based approach successfully generated 80 to 90 percent feedback from the community. Despite the generally low level of education among participants, they demonstrated a good understanding of the material presented by the facilitators. The training began with a presentation on the process of producing wafer feed from sago pulp, followed by a simulation of business cost calculations for traditional cattle farming using a combination of wafer feed and natural grass. The findings also revealed that feed costs using wafer products were more economical, efficient, and generated higher profits compared to natural grass feed. In conclusion, wafer feed is feasible for application in both traditional and conventional cattle farming and holds strong potential for improving the welfare of livestock farmers.